ANALYSIS OF STUDENT LEARNING OUTCOMES IN SDN KALIKUNING 05 DURING ONLINE LEARNING - Lestari, Sri; Anggrasari, Liya Atika; Kurniawan, Nurulloh (JURNAL PENDIDIKAN DASAR NUSANTARA, 2022)
This study aims to determine the learning outcomes of SDN Kalikuning 05 students, especially fourth grade students during online learning. This research is a qualitative research using a descriptive approach. The subjects in this study were 10 students and 1 teacher. Data collection was taken through observation, questionnaires, and direct interviews. The results of this study indicate that when viewed from the learning outcomes the average grade IV students in online learning for the even semester 2020/2021 obtained an average grade value of 78.3. While when compared with the learning outcomes of class students in the odd semester of 74, 6. So the acquisition of student learning outcomes in this even semester has increased. Based on the results of the research above, it can be said that if it is seen that the average value of student learning outcomes in even semesters, online learning can be said to have been effective. However, when viewed from the various problems faced by online learning, it is still less effective and still needs to be improved and considered again, both from teachers and students.